IMPROVEMENT OF THE PSYCHIATRIC CARE THROUGH OUTSOURCING THE ARTIFICIAL INTELLIGENCE TECHNOLOGIES – WHERE ARE WE NOW? - Andrić Petrović, Sanja (Medical Research, 2022)
Currently, the world is entering a fourth industrial revolution – marked by artificial intelligence (AI) powered technologies. The growing ubiquity of AI technologies is already present in many sectors of modern society, but caution still prevails in medicine and its application is far from routine, although it is on the constant rise. Psychiatry has been recognized as one of the disciplines where significant contribution of  AI technologies is expected for the prediction, diagnosis, treatment and monitoring of persons with psychiatric disorders. In over 45% of the world's countries, there is one psychiatrist per 100,000 inhabitants, which is far below the health needs because the prevalence of psychiatric disorders is in the range of 10-20%. Thus, the question arises – whether AI technologies can help to unmet needs in psychiatry? The main types of autonomous  technologies currently applied in psychiatry are machine learning and its subsets deep learning and computer vision, alongside natural language processing and chatbots. The present review will focus on the brief history of the concept, the utility of AI technologies in psychiatry, clinicians’ attitudes,  ethical dilemmas, clinical and scientific challenges. This review emphasizes that the psychiatric community should not be ignorant but could try to leave the comfort zone and do more to raise the awareness of AI technologies development achievements
Keywords: artificial intelligence; machine learning; psychiatry; mental health; ethics